The impact of the resumption of in-person school attendance on COVID-affected child abuse and neglect trends in Florida. (July 2022) - Nguyen, Loc H.
Abstract: Background: The COVID-19 pandemic has led to fewer child abuse and neglect (CAN) hotline calls, CAN investigations, and foster care entries across the U.S. Objective: To determine if there were decreases in CAN hotline calls, CAN investigations, foster care entries, and foster care exits in Florida (the largest among the few states that publishes monthly public data on the four areas) after the pandemic began, and to determine if there was any amelioration of these trends in Florida once schools had reopened for in-person learning. Methods: Secondary data analyses of administrative child welfare data from January 2010 to June 2021 from Florida were used. Spline regression equations were calculated for CAN hotline calls, CAN investigations, foster care entries, and foster care exits during three periods: 1) before the COVID-19 pandemic (January 2010 to February 2020); 2) after the pandemic, but before schools reopened (March 2020 to October 2020); and 3) after the pandemic and after schools reopened (November 2020 to June 2021). Results: Prior to the pandemic, there was a non-statistically significant increase of 1.35 hotline calls per 100, 000 children per month ( p  = .478), a statistically significant increase of 0.01 investigations per 100, 000 children per month ( p  < .001), a non-statistically significant increase of 0.01 foster care entries per 100, 000 children per month ( p  = .415), and a statistically significant increase of 0.03 foster care exits per 100, 000 children per month ( p  < .05). Once the pandemic started in March 2020, there were statistically significant decreases of 136.02 hotline calls per 100, 000 children per month ( p  < .001), 102.84 investigations per 100, 000 children per month ( p  < .001), 6.32 foster care entries per 100, 000 children per month ( p  < .001) and 5.75 foster care exits per 100, 000 children per month ( p  < .01). Once all schools reopened for in-person learning in November 2020, there continued to be statistically significant decreases of 47.86 hotline calls per 100, 000 children per month ( p  < .05), 6.38 foster care entries per 100, 000 children per month ( p  < .001) and 6.53 foster care exits per 100, 000 children per month ( p  < .001). This suggests that there were an estimated 34, 374 fewer CAN hotline calls, 2338 children who did not enter foster care, and 2587 youth residing in foster care (YRFC) whose foster care exits were delayed. The delay in foster care exits suggests that YRFC in Florida had stayed a combined cumulative equivalent of 477.1 years longer in care. Conclusion: With the COVID-19 variants like Omicron continuing to wreak havoc in Florida, there will be a continued trend of decreasing CAN hotline calls, foster care entries and foster care exits even with in-person learning in all Florida schools. A real-time interoperable data system utilizing real-time predictive analytics must be developed in concert with the development of leaders and executives with advanced degrees in child welfare organizations who are able to maximize information from such systems.